TEACHING AND LEARNING OF MATHEMATICS USING CDiCL: MAKING SENSE THROUGH COMPUTERS WITHIN TEAMWORK - Mohd Sazali Khalid; Helmi Adli Mohd Noor (2012)
This book is to address the shortcomings of teaching and learning mathematics and sciences in the world of polytechnic with a product called CDiCL (an acronym to Compact Disk interactive within Collaborative Learning environment) from the lense of the first author teaching three establishments of learning namely schools, Polytechnic Kota Bharu (PKB)  and a university in this country within the span of 25 years. In doing so he delved on some important points like anxiety and misconceptions among teachers and lecturers delivering subjects on ICT while their students look so eager to learn anything from computers. The courseware is designed using ADDIE methodology, complete and been tested fully among 137  polytechnic certificate engineering in March 2006  in Polytechnic Kota Bharu, Kelantan (MoHE) for eight weeks only. Consultants from Deakins University, Australia Dr Heather Mays, Dr Suhaida and Dr Kassim Institut Pendidikan Guru Batu Pahat MoE and feedback from multimedia experts in  2006 2nd WSEAS International Conference in Tenerife Islands, Spain were obtained. The contents is in English as the medium of instruction in higher learning in Malaysia.